Relationships in the interbank market - Jonathan Chiu; Cyril Monnet (Bank of Canada, 2016)
The market for central bank reserves is mainly over-the-counter and exhibits a core-periphery network structure. This paper develops a model of relationship lending in the unsecured interbank market. In equilibrium, a tiered lending network arises endogenously as banks choose to build relationships to insure against liquidity shocks and to economize on the cost to trade in the interbank market. Relationships matter for banks' bidding strategies at the central bank auction and introduce a relationship premium that can significantly distort the observed overnight rate. For example, it can explain some anomalies in the level of interest rates—namely, that banks sometimes trade above (below) the central bank's lending (deposit) rate. The model also helps to explain how monetary policy affects the network structure of the interbank market and its functioning, and how the market responds dynamically to an exit from the floor system. We also use the model to discuss the potential effects of bilateral exposure limits on relationship lending.
Keywords: E4; E5; 330; Interest rates; Monetary policy implementation; Transmission of monetary policy